Juridical Review of Efforts to Prevent Misuse of Firearms Against Police Officers - Diva Fadllan Nur Setiawan (UM Purwokerto Press, 2023)
Lately there have been many police cases, especially violations in the field of firearms abuse. This situation is very regrettable where the misuse of firearms is carried out by the police officers themselves who are supposed to protect the community. This proves the increasingly poor image of the Police in the midst of society. The purpose of this research is to find out the factors causing the misuse of firearms committed by law enforcement officials, especially police officers. The research method used in this research is the literature method, which is normative juridical, meaning that the approach taken by examining the approach of theories, concepts, examining the legislation concerned with the opinions of scholars. The results of this study are factors that cause firearm abuse, namely: Psychological Factors and Economic Factors. Unstable psychological (emotional) factors from police officers, stress due to family problems or other personal problems so that abuse is very easy to occur. While the economic factor is the lack of welfare of the members themselves which then makes a police officer with short thinking do things that are actually very prohibited and have been listed in the law as dangerous criminal acts. Repressively, namely by examining the psychological aspects of the applicant (member), periodically and conducting coaching and training for members who have permission to hold firearms. Repressively is by providing action or punishment in accordance with what is done in accordance with applicable legislation.